2021
DOI: 10.1021/acsomega.0c05516
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Quantum Chemical Methods to Understand the Formation of Concomitant Polymorphs of Acetyl 2-(N-(2-Fluorophenyl)imino)coumarin-3-carboxamide

Abstract: Crystallization of concomitant polymorphs is a very intriguing process that is difficult to be studied experimentally. A comprehensive study of two polymorphic modifications of acetyl 2-(N-(2-fluorophenyl)­imino)­coumarin-3-carboxamide using quantum chemical methods has revealed molecular and crystal structure dependence on crystallization conditions. Fast crystallization associated with a kinetically controlled process results in the formation of a columnar structure with a nonequilibrium molecular conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 57 publications
2
9
1
Order By: Relevance
“…The polymorphic forms I and II have the same packing type (columnar-layered), and the packing of DBUs is more anisotropic in the most stable polymorph I . The obtained regularities between crystal structure stability and the degree of its packing anisotropy correlate with previously published data. , …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The polymorphic forms I and II have the same packing type (columnar-layered), and the packing of DBUs is more anisotropic in the most stable polymorph I . The obtained regularities between crystal structure stability and the degree of its packing anisotropy correlate with previously published data. , …”
Section: Resultssupporting
confidence: 89%
“…The obtained regularities between crystal structure stability and the degree of its packing anisotropy correlate with previously published data. 35 , 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our earlier data, , such interactions of a basic molecule with its environment allow presuming that the polymorphic form 6MU_II is the most stable in comparison with other studied forms. The calculations of the lattice energies in periodic approximation for all of the polymorphic forms under study have revealed that polymorph 6MU_II has the lowest lattice energy.…”
Section: Resultsmentioning
confidence: 99%
“…Several compounds with a central 2-iminocoumarin (2-imino-2 H -chromene)—less known coumarin analogs—are studied for many interesting potential applications due to their optical or fluorescent properties [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Furthermore, it was found that compounds bearing 2-iminocoumarin core possess antimicrobial [ 53 , 54 , 55 ] and anti-inflammatory [ 56 ] activities, or neuroprotective properties, such as BACE1 inhibitors [ 57 ].…”
Section: Introductionmentioning
confidence: 99%